Is Police Integrity an Important Predictor of Citizen Satisfaction in Police in Post-colonial Emerging Democracies? The Case of India - Nalla, Mahesh (Asian journal of criminology, 2018)
The focus of this study is to examine citizen satisfaction with the police. Specifically, the authors aim to understand the factors that determine citizen satisfaction with police services in India, a former English colony and a relatively new republic that has achieved a significant economic development in recent decades. Findings from analysis of a convenience sample (N = 845) obtained from four Northern states in India suggest that perceived procedural fairness, fear of crime, and age of the respondents predict satisfaction with police services. Moreover, perceived professionalism of police officers is found to increase their perceived procedural fairness.